2005
DOI: 10.1136/jcp.2004.023416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p-STAT3 in human colorectal adenocarcinoma and adenoma; correlation with clinicopathological factors

Abstract: Background: The signal transducer and activator of transcription 3 (STAT3) is a key signalling molecule implicated in the regulation of growth and malignant transformation. Constitutive activation of STAT3 is seen in several tumour derived cell lines, and in a wide variety of human malignancies. Aims: To examine the relation between p-STAT3 (activated form of STAT3) expression and clinicopathological factors in human colorectal adenocarcinoma and adenoma. Methods: Immunohistochemical analyses were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
128
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 47 publications
(45 reference statements)
8
128
2
Order By: Relevance
“…The expression of STAT3 in colon adenoma was shown in Figure 2. The activated level of STAT3 was remarkably elevated in patients of CAC; along with STAT3 phosphorylation actively induced the anti-apoptotic genes including Bcl2 and Bcl-xl that also correlated with the tumor invasion, metastasis, and worse prognosis in CAC (Corvinus et al, 2005;Kusaba et al, 2005;Kusaba et al, 2006;Lassmann et al, 2007). Due to the remarkable role played by the STAT3 signaling pathway in intestinal inflammation and CRC, the STAT3 pathway was suggested to be primary and specific targeting pathway in selective therapeutic approach to CAC (Atereya and Neurath, 2008).…”
Section: Regulation Of Stat3 Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…The expression of STAT3 in colon adenoma was shown in Figure 2. The activated level of STAT3 was remarkably elevated in patients of CAC; along with STAT3 phosphorylation actively induced the anti-apoptotic genes including Bcl2 and Bcl-xl that also correlated with the tumor invasion, metastasis, and worse prognosis in CAC (Corvinus et al, 2005;Kusaba et al, 2005;Kusaba et al, 2006;Lassmann et al, 2007). Due to the remarkable role played by the STAT3 signaling pathway in intestinal inflammation and CRC, the STAT3 pathway was suggested to be primary and specific targeting pathway in selective therapeutic approach to CAC (Atereya and Neurath, 2008).…”
Section: Regulation Of Stat3 Pathwaymentioning
confidence: 96%
“…The constitutive activation of STAT3 is frequently discovered in clinical samples from a wide range of human carcinoma and established human cancer cell lines, such as multiple myeloma, glioblastoma, colorectal and hepatocellular carcinoma (Buttner et al, 2002;Corvinus et al, 2005;Kusaba et al, 2005;CarlettFalcone et al, 1999). The expression of STAT3 in colon adenoma was shown in Figure 2.…”
Section: Regulation Of Stat3 Pathwaymentioning
confidence: 99%
“…Suppression of STAT3 expression by small interfering RNA (siRNA) inhibited cell invasion ability and induced anoikis in CRC cells (17). Clinical data also showed that in colorectal adenocarcinoma, the phospho-Tyr-STAT3 (p-STAT3) level was significantly correlated with the depth of tumor invasion, venous invasion, lymph node metastasis, and increasing stages of the Dukes' classification (18,19). Taken together, these findings demonstrate that the STAT3 pathway plays a critical role in the progression of CRC (20)(21)(22).…”
mentioning
confidence: 86%
“…Recently, constitutively activating STAT3 mutations were identified in human hepatocellular adenomas, where the Tyr-640 mutant homodimerizes independently of upstream signals and is hypersensitive to IL-6 stimulation (36). In CRC, STAT3 activation (phosphorylation) was considerably up-regulated during adenoma-to-carcinoma progression (37,38), but the precise role of STAT3 in CRC has not been yet defined.…”
Section: Discussionmentioning
confidence: 99%